Agent-Based Model to simulate Araucaria angustifolia Forest Dynamics as a tool for Forest Management - Valeriano, Diana; Buurman, Merret; Valeriano, Dalton; Amaral, Silvana (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA); 2014: Anais do V Workshop de Computação Aplicada a Gestão do Meio Ambiente e Recursos Naturais, 2014)
The objective of this project was developing an agent-based model to simulate the successional evolution of Araucaria angustifolia [Bertol.) Kuntze (Brazilian pine) in a natural forest stand providing useful information for forest management purpose. Using TerraME as computational framework, the colonization dynamic of Araucaria was represented as an agent with behavior modeled by its life cycle of recruitment, growth, dispersion and death. The model functioning was testing simulating scenarios with and without fires disturbances. Preliminary results are in accordance with conceptual models proposed for these forests. This work emphasizes the modelling relevance, constructing simulated scenarios that can be further integrated into decision making for natural resources management.